Macroeconomic policy in a small open-economy under flexible exchange-rates with bond financing of government deficits - Murray, S (Economic & Social Studies, 1980)
This paper presents a dynamic macroeconomic model of a small open economy (SOE) under flexible exchange rates in which the government offsets its budget imbalances by sales or purchases of its own bonds, the dynamics arising from a stock-adjustment approach to capital movements and from the government's budget constraint. Stability conditions and the medium-run policy multipliers are derived. It is shown that government spending has no effect on income in the medium run but raises income in the short run. Thus, a government wishing to raise income permanently by fiscal policy must absorb an ever-increasing share of output. Monetary policy raises output in the medium run. It is shown that bond financing of government deficits is inherently destabilising in an SOE, producing at best a quasi-steady-state in which the aggregate assets stocks are constant but the composition of the bond stock is changing secularly.
Keywords: Economics; Sociology